Trust Profiles: Associations With Psychological Need Satisfaction, Work Engagement, and Intention to Leave - Heyns, Marita; Rothmann, Sebastiaan (Frontiers in Psychology, 2021)
The study aimed to identify trust profiles in the work domain and to study how these patterns related to psychological need satisfaction, work engagement, and intentions to leave. A cross-sectional survey with a convenience sample (N = 298) was used. The Behavioural Trust Inventory, the Work-related Basic Need Satisfaction Scale, the Work Engagement Scale, and the Turnover Intention Scale were administered. The results showed that four trust profiles, namely, sceptic, reliance-based, disclosure-based, and optimistic trustors, represented the responses of participants on behavioural trust well. Sceptic and optimistic trustors (who represented about 50% of the sample) differed primarily regarding the intensity of their reliance and disclosure. The other two trust profiles (representing the other 50% of the sample) reflected either high reliance and low disclosure, or low reliance and high disclosure. Psychological need satisfaction (comprised of autonomy, competence, and relatedness satisfaction) and work engagement were the strongest and intentions to leave the weakest for optimistic trustors (compared to sceptic trustors).